Enhancing Early Childhood Literacy Skills through Interactive Play-Based Learning at RA Al Falah Pematangsiantar - Devita Mayasari; Lina Sundari Nasutiona (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) investigates the effectiveness of interactive play-based learning in enhancing early childhood literacy skills at RA Al Falah Pematangsiantar. Early childhood education plays a pivotal role in laying the foundation for literacy development, which is critical for a child’s academic and social success. However, many children in RA Al Falah Pematangsiantar face challenges in developing basic literacy skills, particularly in recognizing letters, phonemes, and constructing simple words. This research aims to address these issues by incorporating play-based activities into the learning process to make literacy acquisition more engaging and effective. The study was conducted over two cycles with 25 children aged 4-6 years. During each cycle, the researcher implemented interactive play-based activities, such as letter games, storytelling, and role-playing, to encourage active participation and hands-on learning. Data was collected through observations, interviews with teachers, and literacy assessments. The results showed a noticeable improvement in the children’s ability to recognize letters, understand phonemic awareness, and form basic words. Additionally, children became more confident in their ability to express themselves through verbal communication. This research highlights the importance of using interactive and playful methods to engage young learners in the development of literacy skills. By integrating play into the learning process, children were more motivated and active participants, which enhanced their language development. The study suggests that play-based learning is an effective approach for improving early literacy and should be further explored in early childhood classrooms.